Holocaust in the District of Kėdainiai - Brandišauskas, Valentinas (Genocidas ir rezistencija, 2025)
During World War II the General Commissariat of Lithuania was administratively divided into Commissariats (Ger. Gebiet), which in turn were subdivided into districts (Ger. Kreis), and the latter into rural counties (Lith. valsčius, Ger. Amtsbezirk). The district of Kėdainiai comprised 12 rural counties in which the Jews lived in compact communities.
Keywords: German occupation; Jews; Holocaust; Kėdainiai